2018
DOI: 10.21037/jtd.2018.01.45
|View full text |Cite
|
Sign up to set email alerts
|

Serum osteopontin in patients with lung cancer and chronic obstructive pulmonary disease: does the co-existence make the difference?

Abstract: OPN levels ≥35 ng/mL could predict the presence of LC among COPD patients. In patients with LC and/or COPD, LC is the major determinant for serum OPN. Serum OPN might be a promising prognostic biomarker of LC and a diagnostic biomarker of LC among COPD patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 32 publications
0
6
1
Order By: Relevance
“…Many studies conducted on patients have found increased serum levels of OPN in smokers as compared to non-smokers. 24,[26][27][28] In the present study however, no significant difference in levels of OPN was found between smokers, ex-smokers and non-smokers in patients with ILD as well as COPD. Similar results have been forwarded by a study, where it was found that smoking caused concentration dependent increase in OPN levels in cultured endothelial cells.…”
Section: Discussioncontrasting
confidence: 77%
“…Many studies conducted on patients have found increased serum levels of OPN in smokers as compared to non-smokers. 24,[26][27][28] In the present study however, no significant difference in levels of OPN was found between smokers, ex-smokers and non-smokers in patients with ILD as well as COPD. Similar results have been forwarded by a study, where it was found that smoking caused concentration dependent increase in OPN levels in cultured endothelial cells.…”
Section: Discussioncontrasting
confidence: 77%
“…Some studies describe that advanced stages of NSCLC present higher levels of serum OPN compared to the early stages [111]. However, other studies did not detect a significant difference in OPN concentrations according to TNM classification [154,155]. In those studies, the limited number of patients with early-stage disease may be the cause of a lack of statistical significance, which is more compatible with what is observed in daily clinical practice.…”
Section: Reviewmentioning
confidence: 77%
“…The high AUC value of 0.893 for SPP1 expression level indicated promising utility of SPP1 as a biomarker in the lung for the prediction of LC risk in patients with COPD, although the sample size was not large enough. A previous study using serum OPN to predict cancer risk in patients with COPD identified a rather small AUC value of 0.636 [33]. There are two forms of OPN, intracellular form (iOPN) and a secreted form (sOPN) [34], and sOPN may be produced by many cell types, including hepatocytes, cholangiocytes, hepatic stellate cells, macrophages, T lymphocytes and natural killer T cells [35].…”
Section: Discussionmentioning
confidence: 99%